Do empowerment impacts endure? The medium-term impacts of the Agriculture, Nutrition, and Gender Linkages (ANGeL) Project in Bangladesh - Quisumbing, Agnes R.; Ahmed, Akhter; Hoddinott, John F.; Rakshit, Deboleena (CGIAR System Organization, 2024)
Whether impacts of development interventions are sustainable has attracted much recent interest (examples include Bandiera et al., 2017, Banerjee et al., 2021, Blattman et al., 2020, Carneiro et al., 2021, Grisolia, 2024, and Haushofer and Shapiro, 2018). When interventions involve trained facilitators, for example, it is of interest to know whether effects persist once these facilitators are no longer delivering the message (Ahmed et al, forthcoming). The recognition of women’s empowerment and gender equality as intrinsically important has spawned a growing literature on the impacts of development interventions on women’s empowerment (Quisumbing et al. 2023, Quisumbing et al. 2024) and attitudes towards gender roles (Alderman et al. 2025). Yet, with few exceptions (Alderman et al. 2025) there is little overlap between these two areas of work, in large part because many impact evaluations fail to follow up after the initial evaluation is completed. A synthesis of findings from a portfolio of 11 agricultural development projects in South Asia and Africa suggests that, while projects are able to affect aspects of empowerment such as decisionmaking over resources and control over income, changes in gender norms are more difficult to achieve in the two to three year time span over which impact evaluations are typically conducted(Quisumbing et al. 2024). If women’s empowerment interventions aim ultimately to change gender norms, to detect impacts, they should be measured over a sufficiently long period of time to allow for norm change.